Exploration of IAA and HCN Producing Rhizobacteria from Cassava (Manihot esculenta Crantz) Rhizosphere - Safriani, Suri Raihan; Fitri, Lenni; Ismail, Yulia Sari (Jurnal AgroBiogen, 2020)
Plant growth promoting rhizobacteria (PGPR) are a group of beneficial bacteria that live in rhizosphere. These bacteria can promote plant growth through several mechanisms, such as the ones produce indole-3-acetic acid (IAA) hormone and hydrogen cyanide (HCN), and act as biocontrol agents. The use of PGPR to promote plant growth has been known to be an environmentally friendly alternative approach. The aim of this study was to explore IAA and HCN producing rhizobacteria from cassava rhizosphere soil and identify the bacteria based on morphological and biochemical characters, hypersensitive reaction test, and the ability test to produce IAA and HCN. The results showed nine bacterial isolates suspected as Micrococcus sp. (six isolates), Neisseria sp. (two isolates), and Bacillus sp. (one isolate). All isolates were able to produce IAA in the concentration range of 50,63–135,00 µg/ml and 232,3–333,9 µg/ml at incubation time of 2 and 4 days, respectively. All isolates were able to produce HCN. In addition, the isolates did not show hypersensitivity reactions. Further study is needed to assess the isolate application for promoting plant growth as well as a biocontrol agent of plant pathogen.